Chlamydia trachomatis prevalence in undocumented migrants undergoing voluntary termination of pregnancy: a prospective cohort study - Irion Olivier; Andreoli Nicole; Uny Monique; Epiney Manuella; Bodenmann Patrick; Lourenço Ana; Wolff Hans; Gaspoz Jean-Michel; Dubuisson Jean-Bernard (BMC, 2008)
Abstract Background Chlamydia trachomatis infection (CTI) is the most frequent sexual transmitted disease (STI) in Switzerland but its prevalence in undocumented migrants is unknown. We aimed to compare CTI prevalence among undocumented migrants undergoing termination of pregnancy (ToP) to the prevalence among women with residency permit. Methods This prospective cohort study included all pregnant, undocumented women presenting from March 2005 to October 2006 to the University hospital for ToP. The control group consisted of a systematic sample of pregnant women with legal residency permit coming to the same hospital during the same time period for ToP Results One hundred seventy five undocumented women and 208 women with residency permit (controls) were included in the study. Mean ages were 28.0 y (SD 5.5) and 28.2 y (SD 7.5), respectively (p = 0.77). Undocumented women came primarily from Latin-America (78%). Frequently, they lacked contraception (23%, controls 15%, OR 1.8, 95% CI 1.04;2.9). Thirteen percent of undocumented migrants were found to have CTI (compared to 4.4% of controls; OR 3.2, 95% CI 1.4;7.3). Conclusion This population of undocumented, pregnant migrants consisted primarily of young, Latino-American women. Compared to control women, undocumented migrants showed higher prevalence rates of genital CTI, which indicates that health professionals should consider systematic screening for STI in this population. There is a need to design programs providing better access to treatment and education and to increase migrants' awareness of the importance of contraception and transmission of STI.